Dynamic Viscosity of Purified Multi-Walled Carbon Nanotubes Water and Water-Propylene Glycol-Based Nanofluids. Issue 19 (13th November 2021) - Hamze, Samah; Berrada, Nawal; Desforges, Alexandre; Vigolo, Brigitte; Gleize, Jérôme; Ghanbaja, Jaafar; Maré, Thierry; Cabaleiro, David; Estellé, Patrice
Abstract: We report in this study the experimental investigation of the dynamic viscosity of purified multi-walled carbon nanotubes (MWCNT) water and water-propylene glycol-based nanofluids in the temperature range 10–80 °C. Four weight concentrations of MWCNTs are considered, between 0.005 and 0.1 wt.%. Triton X-100, a common nonionic surfactant, is used to disperse the nanotubes and stabilize the nanofluids as evidenced by optical characterization. Purified and non-damaged MWCNTs are used for nanofluid preparation by the two-step method. MWCNT characterization is deeply investigated from a set of complementary techniques such as thermogravimetric analysis, transmission electron microscopy, and Raman spectroscopy. The studied nanofluids behave as Newtonian fluids for low nanotube content while a shear-thinning behavior is noticed for higher concentration. Finally, the viscosity enhancement of nanofluids with MWCNT loading is compared to the modified Maron–Pierce model considering the presence of aggregates and their size obtained from optical observations.